A new mechanism for improving electromagnetic properties based on tunable crystallographic structures of FeCoNiSixAl0.4 high entropy alloy powders. Issue 27 (19th April 2018) - Zhang, Bin; Duan, Yuping; Cui, Yulong; Ma, Guojia; Wang, Tongmin; Dong, Xinglong
Abstract : Mechanical grinding method was employed to prepare FeCoNiSi x Al0.4 high entropy alloy powders, which present a simple solid solution structure (FCC and BCC). Abstract : Mechanical grinding method was employed to prepare FeCoNiSi x Al0.4 high entropy alloy powders, which present a simple solid solution structure (FCC and BCC). After annealing at 673 K, a large amount of BCC phase precipitate and a small amount of CoFe2 O4 phase generate. The change of crystal structure may lead to an increase in M s (from 100.3 emu g −1 to 124.2 emu g −1 ) and a decrease in H c (from 107 Oe to 59.5 Oe for FeCoNiSi0.3 Al0.4 ). The silica content has a significant effect on the electromagnetic parameters of the as-milled and as-annealed alloy powders, presenting the trend of first increase and then decrease. And the dielectric constant is obviously improved after annealing ( e.g. from 8.48 to 11.21 and from 0.15 to 2.84 for the ε ′ and ε ′′ of FeCoNiSi0.3 Al0.4 at 18 GHz, respectively), while the permeability is reduced. Compared with those of the as-milled samples, the μ ′ of as-annealed FeCoNiSi x Al0.4 ( x = 0.1, 0.3, 0.4) remain unchanged or even increase due to the formation of CoFe2 O4 . Meanwhile, the relative content of the precipitated BCC to FCC for FeCoNiSi0.3 Al0.4 enhance with the annealing temperature increase from 573 K to 773 K, and then reduce. And the ε ′ and μ ′ at 2 GHz present the same trend as the content ratio ( A BCC / A FCC ), while the ε ′′ improve obviously after annealing, corresponding to the elevation of conductivity.